Thermal Performance of T-Shaped Ultra-Thin Vapor Chamber with Double-Sided Heating for LED Automotive Headlamp Cooling - Yaokang Zhang; Tengqing Liu; Yu Bai; Shuangfeng Wang; Qianxi Zhang; Huifeng Kang (Micromachines)
High heat flux brings about severe thermal problems for light-emitting diode (LED) automotive headlamps in narrow heat removal spaces, which will degrade their performance and lifespan. This study proposes an easily fabricated and feasible 1.3 mm thick 2D T-shaped in-plane ultra-thin vapor chamber (UTVC) for cooling the high heat flux of LED automotive headlamps. The effects of heating modes, unequal input heat load, and orientations on the thermal performance of the T-shaped UTVC are investigated. The results show that double-sided heating can improve the temperature uniformity of the T-shaped UTVC and reduce the thermal resistance compared to the single-sided heating. The lowest thermal resistances under single-sided and double-sided heating are 1.127 K/W at 12 W and 0.898 K/W at 16 W, respectively. When the total power is identical, the proposed 2D T-shaped UTVC can work effectively at unequal input power. The orientations have a significant impact on the thermal performance of the 2D T-shaped UTVC, and the thermal performance under different orientations changes with anti-gravity state < horizontal state < gravity-assisted state. The proposed T-shaped UTVC can work effectively under diverse operating ranges.